2, 3, 7, 8-Tetrachlorodibenzo-p-Dioxin and TGF-β3 Mediated-Mouse Embryonic Palatal Mesenchymal Cells. Issue 4 (20th November 2018) - Liyun, Gao; Xu, Jie; Li, Xiao; Wang, Tao; Wu, Weidong; Cao, Jia
2, 3, 7, 8-Tetrachlorodibenzo-p-dioxin (TCDD) is a well-known environmental teratogenic agent for cleft palate. But transforming growth factor β3 (TGF-β3) is an essential growth factor for palatogenesis. This study is to clarify effects of TCDD and TGF-β3 in mouse embryonic palatal mesenchymal (MEPM) cells. The result showed that with increase of TCDD (0.5 nM-10 nM), the expression of TGF-β3 increased, but after 10 nM TCDD, the expression of TGF-β3 reduced. The viabilities of MEPM cells decreased in 10 nM TCDD-treated group. But the viabilities increased in 10 ng/mL TGF-β3-treated group, or the viabilities were between that of them in combination of 10 nM TCDD and 10 ng/mL TGF-β3-treated group. This phenomenon was the same as the motilities. In addition, we found that the expression of phosphorylated Smad2/3 and Smad7 was increased by 10 nM TCDD, 10 ng/mL TGF-β3, or combination of 10 nM TCDD and 10 ng/mL TGF-β3 induced, but the expression of Smad4 was decreased. These data revealed that the TGF-β/Smad signaling pathway affected TCDD and TGF-β3 in MEPM cells.